The Study of Protective Properties of Vaccines against Virulent Strains of the Virus Tick-Borne Encephalitis Three Genotypes: European, Far Eastern and Siberian (Experimental Research) - O. S. Afonina; O. A. Barkhaleva; K. A. Sarkisyan; M. S. Vorobieva; A. A. Movsesyants; Yu. V. Olefir; A. P. Pirozhkov; M. N. Piscov; M. N. Saharov; D. A. Kutaev (Эпидемиология и вакцинопрофилактика)
Researches and presents comparative characteristics of protective properties of vaccines EC domestic and foreign production by immunization line BALB/c mice in a standard experiment for estimating the immunogenic activity against virulent strains of TBE virus three genotypes: genotype 1 - the strain «Sof'in», genotype 2 - strain «Absettarov», genotype 3 - strain «Lesopark». The results are of considerable interest in the evaluation of the efficiency and interchangeability of vaccines for the prevention of TBE in areas of natural foci of the disease in Russia. Currently, the circulation of the pathogen in the Russian Federation dominated by the TBE virus strains Siberian subtype (genotype) -more than 70% of virulent strains of TBE virus released into the natural foci of the Urals, Siberia, the Trans-Baikal. In studies on mice of BALB/c did not reveal significant differences in terms of protection (MID50 and DT50) against virulent strains of TBE virus three genotypes - the Far East, Europe and Siberia for three vaccines: «The vaccine encephalitis culture purified concentrated dry» (production Mikhail Chumakov Federal Research Centre for Research and Development of Immunobiological Preparations, Moscow), EntseVir (production Federal State Unitary Enterprise «Scientific and Production Association «Microgen»), FSME-Immun (Baxter AG production, Austria). Vaccines have shown good protection (protective) properties against 3 genotypes of TBE virus. Revealed a lower protective activity of vaccines Entsepur (manufactured by Novartis Vaccines and Diagnostics GmbH & Co. KG, Germany) strains of TBE 1 and 3 genotypes. These results confirm earlier studies to study the humoral response in mice BALB/c in the experiments with double and triple immunization.